2009
DOI: 10.1016/s1728-869x(09)60024-1
|View full text |Cite
|
Sign up to set email alerts
|

Masters Athletes: An Analysis of Running, Swimming and Cycling Performance by Age and Gender

Abstract: Given the growth in sport participation by masters athletes, the purposes of this paper are to: (1) describe record-level performances of masters athletes in running, swimming and cycling; (2) delineate the age- and gender-related performance decline that occurs in masters athletes in these sports; (3) explain how physiological, sociological and psychological factors affect masters level performance; and (4) provide some tips for continued healthy participation of the masters athlete. World and USA records (cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 46 publications
4
85
2
5
Order By: Relevance
“…[83] In addition, is has been shown that, after 55 years of age, the decline in endurance performance is more pronounced in females than in males. [84] It is thus likely that sex differences in triathlon performance become more pronounced with advancing age. A greater age-related decline in performance in females compared to males has been previously observed in swimming and running.…”
Section: Effects Of Age On Sex Differencesmentioning
confidence: 99%
See 4 more Smart Citations
“…[83] In addition, is has been shown that, after 55 years of age, the decline in endurance performance is more pronounced in females than in males. [84] It is thus likely that sex differences in triathlon performance become more pronounced with advancing age. A greater age-related decline in performance in females compared to males has been previously observed in swimming and running.…”
Section: Effects Of Age On Sex Differencesmentioning
confidence: 99%
“…decline in the thirst mechanism), could affect triathlon performance. [38,83,84,88] In addition, differences in terms of years of training, training volume and intensity between elderly male and female triathletes performing Ironman triathlon may exist, but further research is needed to clarify this. However, interpretation of cross-sectional comparisons of triathlon performance times across ages and sexes must be made carefully.…”
Section: Effects Of Age On Sex Differencesmentioning
confidence: 99%
See 3 more Smart Citations